Historical Dictionary of Witchcraft - Durrant, Jonathan; Bailey, Michael D. (Rowman & Littlefield Publishers, 2012)
Witchcraft has proven an important, if difficult, historical subject to investigate and interpret over the last four decades or so. Modern historical research into witchcraft began as an attempt to tease out the worldview of ordinary people in 16th- and 17th-century England, but it quickly expanded to encompass the history of witchcraft in most cultures and societies that have existed with scholarly studies now extending back to the time of earliest law code that punished sorcery, the Babylonian Code of Hammurabi (1792-1750 B.C.E.), and forward to the last witchcraft cases in England, those of Helen Duncan and Jane Yorke, tried in 1944. There has also been a significant amount of interest in the development of the modern religion of witchcraft, or Wicca, as various forms of neo-paganism continue to attract adherents. The second edition of Historical Dictionary of Witchcraft covers the history of the Witchcraft from 1750 B.C.E. though the modern day. This is done through a chronology, an introductory essay, and an extensive bibliography. The dictionary section has over 300 cross-referenced entries on witch hunts, witchcraft trials, and related practices around the world. This book is an excellent access point for students, researchers, and anyone wanting to know more about the history of witchcraft.